Tingkat Kesehatan pada Koperasi Unit Desa Mambal, Kecamatan Abiansemal, Kabupaten Badung - PRAMANA, I GUSTI MADE AGUNG YUDA; ANTARA, MADE; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.1, Januari 2020, 2020)
Health Rating of Mambal Village Unit Cooperative, Abiansemal Sub-District, Badung Regency Based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No.14/Per M. KUKM/XII/2009, Savings and Loan Cooperative Health Assessment (KSP) is a cooperative condition that deals with aspects of capital, productive asset quality, management, liquidity, efficiency, independence and growth as well as cooperative identity. By reviewing these conditions, the objectives of this study are The health rating of the Mambal Village Unit Cooperative in terms of capital, productive asset quality, management, efficiency, liquidity, independence and growth and cooperative identity in 2015 to 2017. The results of the study show that the assessment of the health level of the Mambal Village Unit Cooperative in 2015-2017 was categorized as quite healthy, because it obtained a mean score of 66.64.Suggestions that can be used as input for the Mambal Village Cooperative Unit, namely cooperative managers should be able to increase the acquisition of pre-tax profits by maximizing income through the participation of members in savings and loan activities by maximizing their own capital. In addition, cooperative managers should improve the ability of cooperatives to serve their members.